Comparative Study of the Single and Double-Stage Thermochemical Pretreatment of Gracilaria sp. for Biogas Feedstock - Prastyo, Elli; Cahyono, Rochim Bakti; Marbelia, Lisendra; Budhijanto, Wiratni (Directorate for Research and Community Services, Institut Teknologi Bandung, 2026)
The objective of this study was to evaluate the effects of single-stage thermochemical pretreatment using sodium hydroxide (NaOH) and a double-stage pretreatment combining NaOH and hydrochloric acid (HCl) on the production of reducing sugars and total phenolic compounds (TPC). The influence of pretreatment duration (30–120 minutes) and solvent concentration (NaOH: 0.2–1 N; HCl: 0.05–0.4 N) at 100 °C was systematically investigated. The results showed that the double-stage pretreatment led to a higher yield of reducing sugars while maintaining relatively low TPC levels. Analysis of variance (ANOVA) revealed that, in the single-stage pretreatment, NaOH concentration had a more pronounced effect than treatment duration. Conversely, in the double-stage pretreatment, duration had a greater influence than HCl concentration. Overall, the double-stage pretreatment, involving NaOH-induced delignification followed by acid-catalyzed hydrolysis, offers a promising strategy for the efficient conversion of macroalgae into reducing sugars while minimizing phenolic compound accumulation.